2022
DOI: 10.1080/19320248.2022.2128961
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and COVID-19 Diagnosis: Findings from a National United States Sample

Abstract: This study explores the association between experiencing food insecurity and COVID-19 diagnosis in the United States, and what sociodemographic characteristics moderate this relationship. We analyzed a national sample of adults in the United States (n=6,475). Multiple logistic regression results revealed respondents experiencing food insecurity had approximately 3.0 times significantly higher odds of a positive COVID-19 diagnosis (Odds Ratio [OR]=2.95, 95% Confidence Interval [CI]=1.38-6.32, p<.01), which rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Our models were not able to adjust for employment; however, prior research using a large national US sample found that individuals who were employed had significantly (three times) higher odds of COVID-19. 13 By contrast, Hispanic older adults with dementia may have had increased odds of COVID-19 because they had the lowest income and highest prevalence of ADL limitations compared with both older White and Black adults in our sample. 14 In fact, a recent study indicated that relative to White older adults, although the odds of COVID-19 were higher for Asian (aOR = 1.68, P = 0.61) and Black (aOR = 1.13, P = 0.73) respondents, they were significantly higher for only Hispanic (aOR = 2.71, P < 0.01) respondents in the NHATS COVID-19 sample.…”
Section: Dementia Statusmentioning
confidence: 61%
See 1 more Smart Citation
“…Our models were not able to adjust for employment; however, prior research using a large national US sample found that individuals who were employed had significantly (three times) higher odds of COVID-19. 13 By contrast, Hispanic older adults with dementia may have had increased odds of COVID-19 because they had the lowest income and highest prevalence of ADL limitations compared with both older White and Black adults in our sample. 14 In fact, a recent study indicated that relative to White older adults, although the odds of COVID-19 were higher for Asian (aOR = 1.68, P = 0.61) and Black (aOR = 1.13, P = 0.73) respondents, they were significantly higher for only Hispanic (aOR = 2.71, P < 0.01) respondents in the NHATS COVID-19 sample.…”
Section: Dementia Statusmentioning
confidence: 61%
“…Our models were not able to adjust for employment; however, prior research using a large national US sample found that individuals who were employed had significantly (three times) higher odds of COVID-19. 13 …”
Section: Discussionmentioning
confidence: 99%